2018
DOI: 10.1002/cbdv.201700434
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Fatty Acids Profile in Eleven Wild Mushrooms of Boletacea and Russulaceae Families

Abstract: Eleven species of wild mushrooms which belong to Boletaceae and Russulaceae families were examined by gas chromatography (GC) and gas chromatography-mass spectrometry (GC/MS) analysis for the presence of fatty acids. As far as we know, the fatty acid profiles of B. purpureus and B. rhodoxanthus were described for the first time. Twenty-six fatty acids were determined. Linoleic (19.5 -72%), oleic (0.11 -64%), palmitic (5.9 -22%) and stearic acids (0.81 -57%) were present in the highest contents. In all samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…Such monodominant PC profiles with 50-80% of 36:4 PC are in accordance with our previous reports and literature data for fatty acid composition in phospholipids of basidiomycetes fungi: C18:2 fatty acid was the only predominant fatty acid in PC of almost all studied fungi, C18:1 does not exceed 20% of total FA [8,[40][41][42]. However, the studies conducted on a large number of basidiomycetes where the total fatty acid composition was analyzed showed that in addition to C18:2 many species are characterized by a predominance of C18:1 fatty acids [43,44]. The ratio of these fatty acids varies widely and does not have a clear taxonomic correlation.…”
Section: Comparative Analyses Typing and Clustering Of Pc Profilessupporting
confidence: 78%
“…Such monodominant PC profiles with 50-80% of 36:4 PC are in accordance with our previous reports and literature data for fatty acid composition in phospholipids of basidiomycetes fungi: C18:2 fatty acid was the only predominant fatty acid in PC of almost all studied fungi, C18:1 does not exceed 20% of total FA [8,[40][41][42]. However, the studies conducted on a large number of basidiomycetes where the total fatty acid composition was analyzed showed that in addition to C18:2 many species are characterized by a predominance of C18:1 fatty acids [43,44]. The ratio of these fatty acids varies widely and does not have a clear taxonomic correlation.…”
Section: Comparative Analyses Typing and Clustering Of Pc Profilessupporting
confidence: 78%
“…Extraction and derivatization of all samples was done according to the method described by Dimitrijevic et al [33] …”
Section: Extraction and Derivatization Samples For Fatty Acidsmentioning
confidence: 99%
“…Mushrooms also provide significant amounts of iron, while the content of bioavailable proteins contained in the dry mass of fruiting bodies is greater than that in most fruits and vegetables. Moreover, fungal proteins contain all exogenous amino acids; thus, mushrooms are often referred to as the 'meat of the forest' (Rajewska & Bałasińska, 2004;Siwulski, Sobieralski, & Sas-Golak, 2014) or the 'meat of the poor' due to the possibility of obtaining them from the natural environment (Dimitrijevic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%